análisis de las estrategias comunicacionales utilizadas por la edeq en procesos de r.s.e. En el año 2012 (2013)
This research Project pretends to analyze the communication strategies employed in the CSR (Corporate Social Responsibility) processes executed by EDEQ during 2.012, identifying and characterizing the strategies used in them. The type of this research study was descriptive, since there were analyzed. Also, the study was performed through a qualitative approach, due to the fact that it was vital to know the views of the employees of the company and if the communicational strategies employed in these processes were effective or not. It was concluded that most EDEQ workers, know the kind of strategies that are carried out for the C.S.R processes but during the application of the instruments it was proved that they do not recognize the application of the strategies on the running processes. The main recommendation was to change the focus of the communicational strategy, as it is understood only as a media issue, and should be seen as an essential element for intervention with communities in order to generate processes of mobilization and apprehension